Pre-Exposure Cybersickness Assessment Within a Chronic Pain Population in Virtual Reality - Brown, Phillip; Powell, Wendy (Frontiers in Virtual Reality, 2021)
Virtual Reality (VR) is being increasingly explored as an adjunctive therapy for distraction from symptoms of chronic pain. However, using VR often causes cybersickness; a condition with symptoms similar to those of motion and simulator sickness. Cybersickness is commonly assessed using self-report questionnaires, such as the Simulator Sickness Questionnaire (SSQ), and is traditionally conducted post-exposure. It’s usually safe to assume a zero baseline of cybersickness as participants are not anticipated to be exhibiting any sickness symptoms pre-exposure. However, amongst populations such as chronic pain patients, it’s not unusual to experience symptoms of their condition or medication which could have a confounding influence on cybersickness symptom reporting. Therefore, in population groups where illness and medication use is common, assuming baseline is not necessarily desirable. This study aimed to investigate cybersickness baseline recordings amongst a chronic pain population, and highlights how deviations from an assumed baseline may incorrectly infer adverse effects arising from VR exposure. A repeated measures study design was used, in which twelve participants were assessed pre and post VR exposure via SSQ. Significant differences were found between actual and assumed pre-exposure baseline scores. Furthermore, we found significant differences between actual and assumed increases in cybersickness scores from baseline to post exposure. This study highlights that clinical sub-populations cannot be assumed to have a zero baseline SSQ score, and this should be taken into consideration when evaluating the usability of VR systems or interventions for participants from different demographics.